1999
DOI: 10.1007/pl00021673
|View full text |Cite
|
Sign up to set email alerts
|

Baryon chiral perturbation theory in manifestly Lorentz invariant form

Abstract: We show that in the presence of massive particles, such as nucleons, the standard low-energy expansion, in powers of meson momenta and light-quark masses, in general converges in only part of the low-energy region. The expansion of the scalar form factor σ(t), for instance, breaks down in the vicinity of t = 4M 2 π . In the language of heavy baryon chiral perturbation theory, the proper behaviour in the threshold region results only if the multiple internal-line insertions generated by relativistic kinematics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
1,038
0
23

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 543 publications
(1,093 citation statements)
references
References 41 publications
32
1,038
0
23
Order By: Relevance
“…The dominant k-independent component of f g 1 is larger by a factor of 5π, roughly an order of magnitude, than the power-counting estimate. The enhancement by a numerical factor of π is a common feature of triangular diagrams [26,[30][31][32][33], while the factor 5 can be traced back to a coherent sum over isospin. The three-pion ∆ vertex also gives rise to the leading irreducible CP-violating 3N potential relevant for the considered 3N systems [8,18], The CP-conserving interactions are here treated non-perturbatively in all orders.…”
Section: Jhep03(2015)104mentioning
confidence: 99%
“…The dominant k-independent component of f g 1 is larger by a factor of 5π, roughly an order of magnitude, than the power-counting estimate. The enhancement by a numerical factor of π is a common feature of triangular diagrams [26,[30][31][32][33], while the factor 5 can be traced back to a coherent sum over isospin. The three-pion ∆ vertex also gives rise to the leading irreducible CP-violating 3N potential relevant for the considered 3N systems [8,18], The CP-conserving interactions are here treated non-perturbatively in all orders.…”
Section: Jhep03(2015)104mentioning
confidence: 99%
“…Vertices in these familes involve only g A and F π , and all dependence on other LECs is concentrated in family III, which begins at O(q 3 ). These LECs can be extracted from subthreshold πN amplitudes [8] and one finds that the components V − C and V + C are very strongly dominated by families I and III, respectively. …”
Section: Nuclear Interactionsmentioning
confidence: 99%
“…and has already been expanded to O(q 4 ) [11,8]. The leading O(q 2 ) contribution comes from a tree diagram proportional to c 1 , whereas corrections at O(q 3 ) and O(q 4 ) are due to loops involving nucleon intermediate states and LECs.…”
Section: Nucleon Sigma-termmentioning
confidence: 99%
See 1 more Smart Citation
“…In the works of Becher and Leutwyler [1] it was shown that the convergence of the chiral expansion of the nucleon scalar form factor, driven by the triangle diagram of Fig. 1, is a delicate issue for values of the momentum transfer t near (2m π ) 2 due to the presence of an anomalous threshold, i.e.…”
Section: Motivation: the Problem In The Heavy Baryon Formalismmentioning
confidence: 99%